An Ecosocial model for the sustainability of vulnerable communities - Belchior-Rocha, H.; Ferreira, J. (Ecosocial Transition of societies – The contribution of social work and social policy, 2016)
This groundbreaking book both explains and expands the growing debate on ecological (environmental) social work at the global level. In order to achieve this, the book strengthens the environmental paradigm in social work and social policy by undertaking further research on theoretical and conceptual clarification as well as distinct reflections on its practical directions. Divided into five parts: concepts; the impact of environmental crises; sustainable communities and lifestyles; food politics; and the profession in transition, this work’s main objective is to place ecological social work as a part of the more comprehensive and interdisciplinary eco-social transition of societies towards sustainability, balancing economic and social development with the limited resources of the natural environment. By focussing on these five core concepts, it shows how social work and social policy contribute to this transition through having a research-based approach and orientation on solutions rather than problem analysis. The book will be of interest to scholars from a broad range of disciplines, including those in social work and social policy, sustainability, economics, agriculture and environmental studies.